SISTEM USAHA TANI JAGUNG PADA GAWANG KELAPA - Yulinar Zubaidah; Ridwan Ridwan; Rafli Munir (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2005)
A research about integrated farming system research for maize among coconut trees was carried out in Tabek Panjang village, Lima Puluh Kota Regency. The objective of the research was to find out the best adaptation of maize variety, hybrid and high yielding of maize composite, combined with zero tillage technology. The data were analyzed by using comparative analysis approach between the improve technology in the technical work (productivity and economic cost, profitable and R/C ratio). The result showed that maize C9 hybrid gave the highest yield 7,34 ton/ha, maize C7 hybrid and Bisma varieties gave yields 6,84 ton/ha and 4,56 ton/ha, respectively. The farm operation analysis showed that maize C9 hybrid gave profit Rp 4,060,000 and R/C 2,24 , maize C7 hybrid Rp 3,561.000 and R/C 2,09 and maize Bisma variety Rp. 1,434,850 R/C ratio 1,46. In general, the result of the a study showed that land preparation with zero tillage system was better for maize C7 and C9 hybrids planted among coconut trees. Keywords: The intercropping farming system, zero tillage